Hierarchiczne uporzadkowanie słownictwa a tradycyjna leksykografia - Mikołajczak-Matyja, Nawoja (Investigationes Linguisticae, 2005)
The paper concerns the role of class inclusion (relation of hyponymy) in structures of paradigmatic dictionaries, especially of thesauri (onomasiological dictionaries). Macrostructures of some French, English and Polish thesauri were analysed and compared.